Condition and zonation of mangrove ecosystems in the small islands around the area crossed by the equatorial line of North Maluku Province - Najamuddin Najamuddin; Abdurrachman Baksir; Nebuchadnezzar Akbar; Firdaut Ismail; Abdul Ajiz Siolimbona; Dondy Arafat; Rustam E Paembonan; Raismin Kotta; Beginer Subhan; Irmalita Tahir; Nyoman MN Natih; Eko S Wibowo; Ikbal Marus; I Wayan Nurjaya; Dietriech Geoffrey Bengen (Depik, 2024)
The South Halmahera Islands feature a comprehensive marine coastal ecology. The ecosystems found were seagrass, mangrove and coral reef ecosystems. The components that sustain the existence of this ecosystem are employed equitably because of its geographical location on the equator. Mangrove ecosystems that provide benefits directly and indirectly to the community. The purpose of this study was to determine the condition of the mangrove ecosystem based on the hemispherical photography method and the type of zonation. Tawabi Island, Kayoa, South Halmahera Regency served as the site of the equator research. The research station is determined as many as 3 stations. Mangrove percent cover canopy using the hemispherical photography and transect quadrant for density. Field data gathering procedures with transects drawn perpendicular from the sea to the land. Zonation characteristics and thickness using zone tracking. Density mangrove using ecology analysis and zonation using canvas 9.0. The results of the research founded were Rhizophora apiculata, Rhizophora mucronata and Sonneratia alba. Mangrove percent cover canopy were good category (75-81%), where station I (75%), station II (81%) and station III (77%). Station I having 600 trees per ha, station II having 500 trees per ha, and station III having 400 trees per ha (low density category). Mangroves were found in 3 zones Sonneratia alba, Rhizophora apiculata and Rhizophora mucronata. The mangrove thickness from sea to land at station I (65 meters), station II (69 meters) and station III (42 meters).Keywords:biodiversitycoastalequator lineHalmaheratropical